PERAN AKTIVITAS EKSTRAKURIKULER DALAM PENGEMBANGAN KETERAMPILAN SOSIAL DAN PRESTASI AKADEMIS SISWA SEKOLAH DASAR: The Role of Extracurricular Activities in Developing Social Skills and Achievement of Elementary School Students - Rizkyka, Adetya Nor; Rizkina, Amalia; Ramadhani, M. Ihsan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research aims to determine (1) the implementation of extracurricular activities and (2) the role of extracurricular activities in shaping students' social skills and achievements at SDN Keliling Benteng Ulu 2. The research method used a qualitative approach. Data collection methods used interviews, observations, and questionnaires. The results show that students' social skills can be developed through Pramuka and Jumat Taqwa activities. These extracurricular activities positively influence students' social skills such as communication, teamwork, leadership, and conflict resolution. Furthermore, some students who have won school or regional competitions are those who are active in Pramuka extracurricular activities. This research emphasizes the importance of schools and teachers in providing a variety of extracurricular opportunities to meet the diverse interests and abilities of students. By actively participating in extracurricular activities, students can develop into individuals with high social competence and academic success.